Liver- and Spleen-Specific Immune Responses in Experimental Leishmania martiniquensis Infection in BALB/c Mice - Sukhumavasi, Woraporn; Kaewamatawong, Theerayuth; Somboonpoonpol, Nawaphat; Jiratanh, Montakan; Wattanamethanont, Juntra; Kaewthamasorn, Morakot; Leelayoova, Saovanee; Tiwananthagorn, Saruda (Frontiers in Veterinary Science, 2021)
Leishmania martiniquensis is a neglected cause of an emerging leishmaniasis in many countries, including France, Germany, Switzerland, the United States of America, Myanmar, and Thailand, with different clinical manifestations ranging from asymptomatic, cutaneous (CL), visceral (VL), and atypically disseminated CL and VL. The persistence of parasites and the recurrence of the disease after treatment are challenges in controlling the disease. To explore efficient prophylaxis and therapy, this study aimed to investigate infection outcome and organ-specific immune responses after inoculation with L. martiniquensis (MHOM/TH/2011/PG; 5x106 promastigotes) in BALB/c mice via intravenous and intraperitoneal routes. A quantitative PCR technique, targeting L. martiniquensis ITS1, was primarily established to estimate the parasite burden. We found that the infection in the liver resolved; however, persistent infection was observed in the spleen. Histopathology with Leishmania-specific immunostaining revealed efficient hepatic granuloma formation, while splenic disorganization with parasitized macrophages at different locations was demonstrated. The mRNA expression of Th1 cytokines (IFN-, TNF-, IL-12p40) and iNOS in the liver and spleen was upregulated. In addition, high expression of IL-10 was observed in the spleen in the chronic phase, revealing a significant moderate correlation with the parasite persistence (r(12)=0.72, P=0.009). Further clarification of the mechanisms of persistent infection and experimental infection in immunosuppressed murine models are warranted.